2015
DOI: 10.1080/00049158.2015.1039953
|View full text |Cite
|
Sign up to set email alerts
|

Processing sawn wood from thinned, unpruned 17-year-oldEucalyptus dunniiin southern China

Abstract: Sixty logs of 17-year-old thinned, unpruned plantation-grown Eucalyptus dunnii representing 10 trees from each of 2 provenances were obtained from a field-trial in central Guangxi Province, China, and processed in a nearby sawmill to produce dried appearance-grade sawn wood suitable for manufacture of short-length flooring. This study's objectives included determining: interrelationships between log end-splitting and growth stress measured on standing trees and important wood behaviour during processing; relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This independence of growth and MFA in E. nitens accords with results from E. pellita (−0.19 ± 0.16; Hung et al (2015)) and E. urophylla (−0.36 ± 0.38; Hein et al (2012)), but not with the significant negative genetic correlation reported in E. globulus (−0.86 ± 0.40; Apiolaza et al (2005)). The recovery of high value veneer and timber may also be affected by two facets of tree architecturebranch size and stem straightness (Blackburn et al 2013;McGavin et al 2015b;Peng et al 2015). In the present study, there was a low and non-significant genetic and phenotypic correlation of MFA with branch size and stem straightness (Table 4).…”
Section: Genetic Correlations With Tree Growth and Formmentioning
confidence: 48%
“…This independence of growth and MFA in E. nitens accords with results from E. pellita (−0.19 ± 0.16; Hung et al (2015)) and E. urophylla (−0.36 ± 0.38; Hein et al (2012)), but not with the significant negative genetic correlation reported in E. globulus (−0.86 ± 0.40; Apiolaza et al (2005)). The recovery of high value veneer and timber may also be affected by two facets of tree architecturebranch size and stem straightness (Blackburn et al 2013;McGavin et al 2015b;Peng et al 2015). In the present study, there was a low and non-significant genetic and phenotypic correlation of MFA with branch size and stem straightness (Table 4).…”
Section: Genetic Correlations With Tree Growth and Formmentioning
confidence: 48%
“…The wood from most species of the genus Eucalyptus has intrinsic characteristics that hinder its processing in sawmills, where growth stresses, which result in top cracks and warping, are the main factors that affect the log splitting (LIMA; STAPE, 2017). There are several techniques that can be adopted both in preparation and in splitting to reduce the manifestations of growth stresses, thus minimizing losses during wood processing (PENG et al, 2015;TOMASELLI, 2002).…”
Section: Introductionmentioning
confidence: 99%